Influence of pre-sowing red laser irradiation of tomato seeds on the initial plant development, salinity stress tolerance, and harvest yield - Rivera-Talamantes, Carlos Francisco deJesús; Michtchenko, Alexandre; González-López, Gabriela; Budagovsky, Andrei V.; Coyac, David Correa-; Acosta, Juan (Emirates Journal of Food and Agriculture, 2022)
This work discusses the laser irradiation effects on tomato seeds (Solanum lycopersicum L), regarding the initial plant development, salinity stress tolerance and harvest yield. The aim of this study was to find an optimal pre-sowing laser irradiation treatment to enhance tomato crop.A diode laser with wavelength of 660 nm and power 100 mW was used, 16 treatments were tested by 4 power densities (0.2, 0.4, 2 and 4 mW cm-2) applied during 4 exposure times (15, 30, 60, 120 s) and a control group without treatment. The study was divided into three stages,firstly it was selected an optimal laser treatment (04 mW cm-2, 30 s), in the second stage the optimal laser treatment was evaluated under salinity stress, and finally in the third stage the optimal laser treatment was evaluated on harvest yield. The optimal laser treatment, on the initial plant development enhanced germination by 10%, radicle growth by 19%, and hypocotyl growth by 13%, in comparison to the control. On seedlings under salinity stress, optimal laser treatment promote germination up to 20%, radicle growth up to 23%, and hypocotyl growth up to 12%.According to this study, saline stress inhibits PSII activity in tomato seedlings,whereas optimal laser treatment increased PSII activity around 71%. About greenhouse crop, optimal laser treatment improved mass produced by 26%. The present study shows a path for application ofpre-sowing red laser radiation treatments in tomato seeds to improve development, saline stress tolerance and final production of tomato crop.